TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) TERHADAP PEMALSUAN IDENTITAS DALAM PEMBUATAN AKTA JUAL BELI - Raja Aulia Ayatullah (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT      By carrying out a sale and purchase before the PPAT, the conditions are bright (not a dark legal act, which is carried out clandestinely)."In order to make a deed of sale and purchase of land, the party transferring the right must meet the requirements, namely the authority to transfer the right, while the party receiving it must meet the requirements of the subject of the land to be purchased, and must be witnessed by at least two witnesses of this research. using normative research methods, with the results of research and discussion, namely PPAT's responsibility for the sale and purchase deed he made that was not in accordance with the PPAT deed making procedure or was proven to have committed a violation in carrying out his duties and positions so that the deed he made contained legal defects based on irregularities the formal requirements and material requirements of the procedure for making the PPAT deed, the PPAT may be subject to or imposed sanctions, namely administrative and criminal.Keywords: PPAT, Identity Forgery, Sanctions